Treatment of Pak-India Relations Issues in Indian Press Comparative Study of Editorials of “THE HINDU” & “THE TELEGRAPH” - Shabir, Ghulam; Khan, Abdul Wajid; Safdar, Ghulam; Malik, Adnan (2017)
This research relates to investigate that how Pak-India relations issues represented and portrayed in two leading Indian newspapers.In this article the topics which discussed are Kashmir, Peace Talk and Terrorism.For this purpose, two elite newspapers of India The Hindu and The Telegraph have been selected for the research.This study analyzed the editorials of both newspapers published from 1st January 2006 to 1st December 2009.Theoretical inspiration is drawn from the postulates of agenda setting and framing theory.This research study has employed a combination of the quantitative and qualitative techniques of content analysis to analyze the contents